The Development of the TANDAR project - Mariscotti, Mario A. J.; Ventura, Edgardo; Cevallos, A. E.; Fazzini, N. A.; Filevich, Alberto; González, Hipólito; Requejo, Ricardo; Ribarich, R. B.; Rossi, J. J.; Achterberg, Erhard O. J.; Camín, D. V.; Milber, Jorge; et al. (Oak Ridge National Laboratory. Holifield Heavy Ion Research Facility, 1981)
Fil: Mariscotti, M. A. J. Comisión Nacional de Energía Atómica; Argentina